End-to-end arterial anastomosis with fibrin glue in larger arteries: histology, hydroxyproline concentration and tensile strength study in carotids of rabbits - Yoshida,Winston B. (2002)
End-to-end conventional arterial anastomosis is time consuming, requires prolonged clamping times and is associated with focal necrosis, granulocyte infiltration and subsequently, fibrosis and calcification of the arterial wall. Fibrin glue as an alternative for microarterial anastomosis may obviate these lesions, with less adherence to adjacent tissues and better coaptation of the arterial margins. OBJECTIVE: In this study we compared the healing process of conventional to fibrin glue end-to-end anastomosis in larger arteries. METHODS: In 22 rabbits, both carotid arteries were cross sectioned and repaired by end-to-end anastomosis with 4 interrupted sutures and fibrin glue in one side (GI) and with 8 conventional interrupted sutures in the other side (G2). After 3 and 15 days, the animals were randomly allocated for tensile strength, hydroxyproline determination (8 animals), and histologic analysis of the anastomosis (3 animals). Conventional staining procedures (hematoxylin-eosin and Masson methods) and picrosirius red polarization (PSP) technique for collagen type determination were employed. RESULTS: From 3 to 15 days, the tensile strength increased in both groups, from 280.0± 32.6 g to 432.2± 131.2g in Group I and from 221.4± 72.4g to 452.2± 132.0g in Group 2 (p<0.001), with no statistical difference between the groups in each period of the study. The hydroxyproline content, expressed as hydroxyproline /protein ratio, varied from 0.0816 ± 0.0651 to 0.0622 ± 0.0184 in Group l and from 0.0734 ± 0.0577 to 0.0460 ± 0.0271 in Group 2, with no significant difference between periods and groups (p>0.05). Histology showed slight increase of inflammatory and reparative reactions in Group 2. PSP technique demonstrated predominant type I collagen in relation to type III collagen in the anastomosis of both groups, with no significant difference between them. CONCLUSION: Fibrin glue was less harmful to the arterial wall than conventional suture. Even using less sutures in fibrin glue anastomosis, similar tensile strength and healing characteristics were noted in both groups. Completion times for the fibrin glue group was significantly greater than for the conventional anastomosis.